2015
DOI: 10.1007/s10212-015-0261-x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of effortful control and empathy on perception of school climate

Abstract: The purpose of this study was to determine the predictive power of effortful control (EC) and empathy for perception of school climate. Self-report measures of EC, dispositional empathy, and perception of school climate were obtained for 398 students (204 females) aged 12 to 13. Sociometric status was peer-evaluated, and academic achievement was based on students final grades at the end of the school year. The structural equation model that was developed confirms the influence of EC and empathy on perception o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 55 publications
1
13
0
Order By: Relevance
“…This confirms that, apart from the mediation of empathic socioemotional processes, control and self-regulation skills in themselves enhance social skills and acceptance by peers. Previous studies have also revealed this relationship (Zorza et al, 2013;Zorza et al, 2015). This seems to suggest that self-regulation processes promote respect for group norms and decrease impulsive behaviors (Eisenberg, Valiente, & Eggum, 2010;Eisenberg, Spinrad, & Eggum, 2010;Rueda et al, 2010).…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…This confirms that, apart from the mediation of empathic socioemotional processes, control and self-regulation skills in themselves enhance social skills and acceptance by peers. Previous studies have also revealed this relationship (Zorza et al, 2013;Zorza et al, 2015). This seems to suggest that self-regulation processes promote respect for group norms and decrease impulsive behaviors (Eisenberg, Valiente, & Eggum, 2010;Eisenberg, Spinrad, & Eggum, 2010;Rueda et al, 2010).…”
Section: Discussionmentioning
confidence: 63%
“…EFs and EC may positively influence the social behavior of students by providing empathy. In fact, students who show concern about the emotions of others and perform prosocial behaviors are more favored and accepted by their peers and have a more positive perception of the social climate than those who do not (LaFontana & Cillessen, 2002; Zorza, Marino, & Acosta Mesas, 2015).…”
Section: Control Processes Empathy and Social Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…Study habits, class participation or teacher-student relationship are also highly relevant for the students’ academic performance (Eisenberg, Valiente, & Eggum, 2010; Valiente, Swanson, & Lemery-Chalfant, 2012). Empathy has a direct influence on the students’ interpersonal relationships (Immordino-Yang, 2011; Valiente, Lemery-Chalfant, & Swanson, 2010; Zorza, Marino, & Mesas, 2015), which improves their immersion in the classroom. It is possible that the predictive power of the EFs on academic performance and on social behavior increases when these variables are added in a multicausal way.…”
Section: Discussionmentioning
confidence: 99%
“…The study showed that empathy has infl uence on better study results of the students. But the infl uence of empathy on the climate was considered arguable (Zorza & Marino, 2015). It can be stated, with respect to the research of school climate, that it may constitute a source of information on many educator phenomena and areas.…”
Section: Research Of School Climatementioning
confidence: 99%